Habitat use and locomotion of the François' langur (Trachypithecus francoisi) in limestone habitats of Nonggang, China. Issue 4 (31st October 2012) - ZHOU, Qihai; LUO, Bang; WEI, Fuwen; HUANG, Chengming
Abstract We collected data on habitat use and locomotion of the François' langur (Trachypithecus francoisi) between August 2003 and July 2004 at Nonggang Nature Reserve, China. A total of 739 h of behavioral data were collected during this study. We tested 2 predictions: (1) that the langurs may have special patterns of habitat use and locomotion adaptive to the limestone habitat, and (2) the langurs may exhibit different patterns of habitat use and locomotion among different zones of limestone hill. Our results indicated that François– langurs spent more time in the low‐risk, relatively food‐poor cliff–hilltop areas. When young leaves and fruit were scarce in the dry season, the langurs increased their time in the high‐risk, food‐rich valley basin. François– langurs were semi‐terrestrial, and leaping and climbing were their main locomotor modes. These behavioral patterns are considered to be related to characteristics of topography and vegetation in limestone habitat, such as large areas of cliff and discontinuous canopy. Our results also supported Prediction 2. The langurs confined locomotion to the main canopy and frequently adopted leaping while traveling in the hillside and valley basin. While traveling in cliff–hilltop areas, they tended to stay in the lower stratus (≤5 m) or move on the ground, and walking and climbing were their dominant traveling modes.